Performance evaluation of improved cook stove using briquette as fuel - Verma P.; Shukla S.K. (My University, 2025)
Around 10% of the world's total energy consumption is attributed to cooking of food. In many countries, cooking energy accounts for over 90% of household energy consumption. Variety of biomass fuels is used particularly in developing countries where the majority of population has no access to electricity. This has led to a tremendous increase in fuel consumption and pollution level. The experimental analysis is carried out with the modified design of the cook stove and use of cleaner fuel-briquette with bagasse as binder. In order to know the performance water boiling test was conducted. The observations were used to evaluate stove performance in various aspects, specific fuel consumption and thermal efficiency being the major ones. It was found from experiment that the thermal efficiency achieved is 46.11% and 44.29% for cold phase and hot phase. It was then compared with a parabolic dish type concentrator solar cooker, tested in same environmental conditions with Pugh matrix. The comparison result shows that modified cook stove is better in terms of reliability, capacity and duration of cooking but in terms of pollution, the solar cooker is more effective. © 2019 Author(s).